Respuesta :
Hello,
A is your answer
(-3,6) must be a point of the curve.
A) if x=-3 then y=-3(-3+3)²+6=6
y'=-3(x+3)=0==>x=-3
and y=6
B) if x=-3 then y=-3(-3+3)²-6=-6 and not 6
C) if x=-3 then y=-3(-3-3)²+6=-3*36+6= -102 and not 6
D) -3(-3-3)²-6=-3*36-6=-114
A is your answer
(-3,6) must be a point of the curve.
A) if x=-3 then y=-3(-3+3)²+6=6
y'=-3(x+3)=0==>x=-3
and y=6
B) if x=-3 then y=-3(-3+3)²-6=-6 and not 6
C) if x=-3 then y=-3(-3-3)²+6=-3*36+6= -102 and not 6
D) -3(-3-3)²-6=-3*36-6=-114
Based on the calculations, the equation of this parabola is equal to: A. y = -3(x + 3)² + 6.
How to determine the equation of a parabola?
Mathematically, the standard equation with the vertex for any parabola is given by:
y = a(x - h)² + k.
where:
- h and k are the vertex.
- a is a point.
Substituting the given parameters into the formula, we have;
y = -3(-3 - (-3))² + 6
y = -3(x + 3)² + 6
Read more on parabola here: https://brainly.com/question/2346582
#SPJ5